The Clinical Epidemiology of Spontaneous ICH in a Sub-Sahara African Country in the CT Scan Era: A Neurosurgical In-Hospital Cross-Sectional Survey - Adeleye, Amos Olufemi; Osazuwa, Uyiosa A.; Ogbole, Godwin I. (Frontiers in Neurology, 2015)
Background There is paucity of data-driven scientific reports from sub-Saharan Africa on the burden of spontaneous intracerebral haemorrhage (sICH). We have maintained a prospective consecutive in-hospital data base of cases of sICH referred for neurosurgical intervention over a 5-year period. Methods This is a cross-sectional descriptive study of the clinical epidemiology and brain-CT characterization of sICH from the data base in this region in the current era. Results There were 63 subjects, 38 (60.3%) males, aged 28 to 85 years, mean 55.7 (SD, 12.7), the modal age distribution being the sixth decade. Uncontrolled hypertension was the main predisposition in the study: present, premorbid, in 79% but uncontrolled in 88% of these known cases, and exhibited malignant derangements of blood pressure in more than half. The clinical ictus to in-hospital presentation was delayed, median 72 hours; was in severe clinical state in 70%; 57% was comatose, and was complicated with fever in 57% and respiratory morbidity also in 55.6%. The main clinical symptomatology was hemiparesis, headache, vomiting and aphasia. The sICH was supratentorial on brain CT in 85.7%, ganglionic in 50.8% and thalamic in 58.3% of the latter. The bleed had CT evidence of mass effect and intraventricular extension in more than half. Twenty three patients (36.5%) underwent operative interventions Conclusions In this patient population, sICH is mainly ganglionic and thalamic in location with significant rate of associated IVH. In-hospital clinical presentation is delayed and in critical state, and, the bleeding is uncontrolled hypertension related in >95%.